Ambiente virtual de aprendizagem em ondas e acústica para auxiliar o processo ensino e aprendizagem da física no ensino médio - Carmo, Rodrigo Salvadori Baptista do (Universidade Federal de São Carlos, 2013)
This work describes the development of a VLE Virtual Learning Environment, where music is the basis for studying sound waves. New educational tools such as videos, animations, simulations, as well as the Moodle platform, were used to create a virtual environment, where students can learn about sound waves in an autonomous and interactive way, motivating them to use computers and internet as facilitators of the teaching/learning process, making it more effective and interesting. This material was applied to High School students - which translates to Ensino Médio and/or Pré-Vestibular in Brazil s schooling system - in the following schools: Carlos Drummond de Andrade and Nomelini Cirandinha, both in Barretos, Escola Espaço Livre, in Bebedouro and Coc Cardiofísico, in Jaboticabal. Both the teaching experience related to the VLE construction and its learning results are also described in this work.
Keywords: Física - estudo e ensino; Física ensino; Ondas (Física); Acústica; Música; AVA Ambiente Virtual de Aprendizagem; Physics teaching; Waves and acoustics; VLE Virtual Learning Environment; Music; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA::FISICA MATEMATICA